Reprogramming fibroblasts to pluripotency using arginine-terminated polyamidoamine nanoparticles based non-viral gene delivery system - Zhu K (Dove Medical Press, 2014)
Kai Zhu,1,2,* Jun Li,1,2,* Hao Lai,1,2 Cheng Yang,1,2 Changfa Guo,1,2 Chunsheng Wang1,2 1Department of Cardiac Surgery, Zhongshan Hospital, Fudan University, 2Shanghai Institute of Cardiovascular Disease, Shanghai, People’s Republic of China *These authors contributed equally to this article Abstract: Induced pluripotent stem cells (iPSCs) have attracted keen interest in regenerative medicine. The generation of iPSCs from somatic cells can be achieved by the delivery of defined transcription factor (Oct4, Sox2, Klf4, and c-Myc[OSKM]). However, most instances of iPSC-generation have been achieved by potentially harmful genome-integrating viral vectors. Here we report the generation of iPSCs from mouse embryonic fibroblasts (MEFs) using arginine-terminated generation 4 polyamidoamine (G4Arg) nanoparticles as a nonviral transfection vector for the delivery of a single plasmid construct carrying OSKM (pOSKM). Our results showed that G4Arg nanoparticles delivered pOSKM into MEFs at a significantly higher transfection efficiency than did conventional transfection reagents. After serial transfections of pOSKM-encapsulated G4Arg nanoparticles, we successfully generated iPSCs from MEFs. Our study demonstrates that G4Arg nanoparticles may be a promising candidate for generating of virus-free iPSCs that have great potential for clinical application. Keywords: mouse embryonic fibroblasts, induced pluripotent stem cells